Analysis of the Effectiveness of Village Fund Management in Bone District, South Sulawesi - Andi Samsir (PINISI Discretion Review, 2022)
The purpose of this study was to determine the effectiveness of village fund management in Bone District, South Sulawesi. Based on the research problems stated earlier, the basic methods used in this research are descriptive research. Regarding the descriptive method, it describes how the process of economic development planning in villages in Bone District, South Sulawesi. The types of data used in this study are primary and secondary data obtained by direct observation at the research site and conducting interviews with relevant stakeholders, while secondary data is obtained from literature studies, reports from related agencies and data from the village office or other sources. support this research. Interview technique was used to collect data from respondents by means of questions and answers that were carried out systematically and based on research objectives with tools in the form of questionnaires and interview guidelines (in-depth interviews). Then observation is in the form of data collection techniques where the researcher makes observations directly related to empirical data from research variables. Based on the results of the research and discussion that have been described, it can be concluded that the management of village funds in Bone Regency is categorized as effective.